Dietary Adherence among Patients with Type 2 Diabetes Mellitus in Relation with Family Support in Cipondoh Primary Health Center Tangerang - Diska Dwi Lestari; Karina Megasari Winahyu; Samsul Anwar (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2018)
Background: Diabetes mellitus is one of the most common chronic diseases in the world. The effect of high sugar conditions can cause complications and death. One of the primary management of diabetes mellitus is diet.Aim: The study aimed to identify the relationship between family supports and dietary adherence among patients with type 2 diabetes mellitus in Cipondoh Primary Health Center in Tangerang.Methods: The study used an analytic descriptive design with a Cross-Sectional approach. The study used Dietary Adherence and Hensarling Diabetes Family Support Scale questioners. The sample size was 114 respondents who were recruited by Purposive Sampling. The analysis technique used for this study was the Pearson Product Moment Correlation Coefficient. The study showed that 57,9% have good family supports and most of the patients have good dietary adherence (83,3 %). Results: The result of the statistic test of Pearson Product Moment Correlation Coefficient showed that there was positive relationship between family supports and dietary adherence among patients with Type 2 Diabetes Mellitus in Cipondoh Primary Health Center Tangerang. Conclusion: It suggests that family support has a role to improve dietary adherence of patients with Type 2 Diabetes Mellitus. Healthcare provider needs to maintain family supports in order to keep the diabetic’s dietary adherence. Keywords: Dietary Adherence, Family Support, Type 2 Diabetes Mellitus